The Concept of the Ideal Teacher in the Qur'an: A Tarbawi Tafsir Study on the Figures of the Prophets as Educators - Junaedi Junaedi (Tasyri’: Jurnal Tarbiyah – Syari’ah Islamiyah, 2026)
Education occupies a central role in Islamic civilization, and the figure of the teacher (mu'allim/murabbi) is accorded extraordinary importance within both the Qur'anic worldview and the classical Islamic scholarly tradition. Despite this significance, systematic tarbawi tafsir analysis that interrogates prophetic narratives specifically as models of ideal teaching remains limited. Objective: This study aims to identify, analyze, and synthesize the characteristics of the ideal teacher as conceptualized in the Qur'an through a thematic study of three key prophetic figures: Ibrahim (Abraham), Luqman al-Hakim, and Muhammad (PBUH). Method: A qualitative library research methodology is employed, utilizing the mawdu'i (thematic) tafsir approach as systematized by al-Farmawi to gather, arrange, and interpret all Qur'anic verses pertaining to prophetic educational roles. Primary sources include the major classical and contemporary tafsir works alongside classical texts of Islamic educational philosophy. Findings: The Qur'an presents prophetic figures as possessing six core characteristics of the ideal teacher: (1) profound and integrated mastery of knowledge ('ilm), (2) exemplary personal character (uswah hasanah), (3) wisdom in pedagogical method (hikmah), (4) sincere devotion and God-consciousness (ikhlas and taqwa), (5) compassionate care for learners (rahmah), and (6) a commitment to holistic human development (insaniyyah kulliyyah). Conclusion: These Qur'anic principles constitute a comprehensive and transcendent model of ideal educatorship that enriches contemporary Islamic education theory and provides a corrective to reductive models of teaching that privilege technical competence over moral and spiritual formation. The prophetic educational model uniquely bridges the cognitive, affective, and spiritual dimensions of human personhood.